2021
DOI: 10.3389/fnagi.2021.777819
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Incontinence and Alzheimer’s Disease: Insights From Patients and Preclinical Models

Abstract: Alzheimer’s disease effects a large percentage of elderly dementia patients and is diagnosed on the basis of amyloid plaques and neurofibrillary tangles (NFTs) present in the brain. Urinary incontinence (UI) is often found in the elderly populations and multiple studies have shown that it is more common in Alzheimer’s disease patients than those with normal cognitive function. However, the link between increased UI and Alzheimer’s disease is still unclear. Amyloid plaques and NFTs present in micturition center… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…Indeed, higher neuroticism and lower conscientiousness, and to a lesser extent lower extraversion, openness, and agreeableness, are associated with a higher risk of cognitive impairment and dementia, 19 which are implicated in elevated risk of UI. 31 These traits may also contribute to UI through biological factors. Higher neuroticism and lower conscientiousness, for example, are associated with higher inflammation, 32 which in turn is related to overactive bladder.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, higher neuroticism and lower conscientiousness, and to a lesser extent lower extraversion, openness, and agreeableness, are associated with a higher risk of cognitive impairment and dementia, 19 which are implicated in elevated risk of UI. 31 These traits may also contribute to UI through biological factors. Higher neuroticism and lower conscientiousness, for example, are associated with higher inflammation, 32 which in turn is related to overactive bladder.…”
Section: Discussionmentioning
confidence: 99%
“…Cognitive function may also be a potential pathway that links personality to UI. Indeed, higher neuroticism and lower conscientiousness, and to a lesser extent lower extraversion, openness, and agreeableness, are associated with a higher risk of cognitive impairment and dementia, 19 which are implicated in elevated risk of UI 31 . These traits may also contribute to UI through biological factors.…”
Section: Discussionmentioning
confidence: 99%
“…Once thought to primarily occur in only late-stage disease, many studies have shown emergence of these symptoms in many individuals quickly after diagnosis ( Lyketsos et al, 2011 ). As progression continues, individuals become less able to perform basic activities of daily living (ADLs) and instrumental activities of daily living (IADLs) and become increasingly reliant on caregivers as they develop incontinence and express extrapyramidal symptoms ( Tsolaki et al, 2001 ; Bartolone et al, 2021 ). Once diagnosed, AD will continue to increase in severity over a span of 3–10 years ( Zanetti et al, 2009 ).…”
Section: Diagnosis and Challengesmentioning
confidence: 99%
“…Lower urinary tract dysfunction (LUTD) such as urinary incontinence is prevalent in middle-to late-stage AD. [4][5][6] Although cognitive impairment has been proposed to be associated with abnormal urinary incidents, 7 the underlying mechanistic connection between AD development and the associated bladder disorders is unknown. Recent studies have brought to attention the involvement of spinal cord in AD pathogenesis.…”
Section: Introductionmentioning
confidence: 99%